KEKUATAN SASTRA, LITERASI MEDIA, DAN TOKOH AGAMA DALAM MENANGKAL BAHAYA RADIKALISME - Hasanah, Nurul (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Terminology of radicalism is so many, but the essence is there is contradiction between the values which is fought by a particular religious group with the order of values prevailing at the time. The act of radicalism is not a mistake of a particular religiousâs doctrine, but a misconception of the religion that is embraced. The efforts to ward off and fight radicalism must continue to be done. There are three attempts to ward off the danger of radicalism through literary powers, media literacy, and religious leaders. Literature is a human inner expression that cannot be expressed in plain language. Furthermore, the humanist side of the literary world is able to make a person more wise and wise in dealing with something. In addition to literary power, media literacy, especially social media is considered as very important for the community. Not only gives a positive impact, but also has a negative impact. Social Media has a tendency as a means of disseminating false information content or false news (hoaxes). Related to the process of radicalization, not only born from a group that has direct contact with the perpetrators, but can also be obtained through the internet site. Finally, the role of religious leaders. Religious figures can give an understanding of the doctrine of religious values that lead to peace. This is because the essence of religion that never teaches people to hate each other, or even to do a violence.